Refractory mortar for blast furnace ceramic cup as well as preparation method and construction method of refractory mortar

By using specific combinations of refractory mud raw materials and vacuum filling construction methods, the problems of poor fluidity and poor construction quality of refractory mud for ceramic cups are solved, and higher mud density and strength are achieved, brick joints are reduced, and brick joints are enhanced. The resistance to high-temperature molten iron extends the service life of the blast furnace cylinder.

CN119462101AActive Publication Date: 2025-02-18WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411558377.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing refractory mud for ceramic cups has poor fluidity and poor construction quality and performance, resulting in large brick joints and loose mud, and high-temperature molten iron is prone to permeation and erosion, shortening the service life of the blast furnace furnace cylinder.

Method used

Using raw materials such as microporous corundum powder, silicon aluminum alloy powder, silicon oxynitride microcrystalline powder, activated alumina micropowder, carbon black fine powder, alumina fiber, ammonium polyacrylate and acid zirconia sol, through uniform mixing and stirring , high-flow refractory slurry was prepared, and vacuum filling was used to fill the gaps in the ceramic cup bricks.

Benefits of technology

The density and strength of the refractory mud is improved, the brick joints are reduced from 3mm to 1.5mm, the resistance to high-temperature molten iron is enhanced, and the service life of the blast furnace cylinder is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117184750000021
    Figure BDA0005117184750000021
  • Figure BDA0005117184750000051
    Figure BDA0005117184750000051
  • Figure BDA0005117184750000052
    Figure BDA0005117184750000052
Patent Text Reader

Abstract

The invention discloses refractory mortar for a blast furnace ceramic cup as well as a preparation method and a construction method of the refractory mortar, and belongs to the technical field of refractory mortar. The refractory mortar comprises the following raw material components in percentage by mass: 25-35% of 0.074-0mm microporous corundum fine powder; 25-30% of activated aluminum oxide micro powder; 5-8% of silicon oxynitride microcrystalline powder; 10-20% of alumina fiber; 10-15% of silicon-aluminum alloy powder; 5-8% of carbon black N990; 0.5-1.5% of a polyacrylic acid ammonium salt dispersing agent; and 8-10% of acidic zirconium dioxide sol (additional). The refractory mortar is good in flowability, the construction method is simple and efficient, blast furnace ceramic cup brick joints can be fully filled, the brick joints can meet the construction requirement when the brick joints are 1.5 mm, and the phenomenon that high-temperature molten iron permeates and erodes from the brick joints due to the fact that the building joints are too large and the loose pattern of the building joint mortar is effectively resisted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory mud, and in particular relates to refractory mud for blast furnace ceramic cups and a preparation method and a construction method thereof. Background Art

[0002] The use effect of the blast furnace hearth is an important factor that determines the service life of a blast furnace. When constructing the bottom of the blast furnace, the outermost steel shell is constructed first, and a circle of cup-shaped carbon bricks are built inside the steel shell. A ceramic cup structure is then built inside the carbon bricks to hold high-temperature molten iron. The ceramic cup blocks the 1150℃ isotherm (i.e., the solidification line of molten iron) in the ceramic layer, allowing the bottom carbon bricks to avoid the brittle fracture zone of 800-1100℃. Due to the presence of the ceramic cup, the molten iron does not directly contact the carbon bricks, and the structural design alleviates the penetration and scouring damage of molten iron and alkali metals to the carbon bricks, which can effectively extend the service life of the blast furnace hearth.

[0003] Ceramic coasters use large corundum prefabricated blocks or corundum bricks with self-locking structures, and the ceramic cup wall uses large prefabricated blocks with special shapes, wings on the left and right, and upper and lower layers inserted into the bite. The traditional construction method uses masonry construction, and the matching refractory mud generally has no fluidity. Ceramic cup bricks or prefabricated blocks are heavy and irregular in shape. The bricks or prefabricated parts must be installed to the correct position through mechanical lifting, and the mud must be kneaded by external force to fill the gap between the two bricks. Therefore, a larger brick joint must be designed to meet the construction requirements. Generally, the ceramic cup brick joint is designed to be 3mm. As we all know, there are two problems with refractory mud for ceramic cups. One is that the mud filled between the brick joints and the density, strength and other properties of the masonry bricks are quite different. Secondly, during masonry construction, construction workers need to be very skilled in controlling the amount of mud applied to different positions of prefabricated parts. In addition, due to the large porosity of bricks or prefabricated parts, strong water absorption, and rapid drying of mud, it is necessary to put the prefabricated parts coated with mud in place as soon as possible, otherwise the mud will lose water quickly, forming more "speckles", and the mud fullness will not meet the requirements. The above reasons make the construction quality and performance of refractory mud the weak point of the entire masonry, and high-temperature molten iron is more likely to penetrate through the brick joints and disintegrate the ceramic cup. Therefore, how to reduce the brick joints and improve the density and strength of the refractory mud and the mud's resistance to molten iron corrosion is a top priority. Summary of the invention

[0004] The purpose of the present invention is to provide a refractory slurry for blast furnace ceramic cups and a preparation method and a construction method thereof. The refractory slurry has good fluidity, a simple and efficient construction method, and can fully fill the brick joints of the blast furnace ceramic cups. The brick joints of 1.5 mm can meet the construction requirements, and effectively resist the penetration and erosion of high-temperature molten iron from the brick joints caused by excessive masonry joints and loose masonry mud.

[0005] To achieve the above object, the technical solution of the present invention is:

[0006] Provided is a refractory slurry for a blast furnace ceramic cup, wherein the raw material components are, by mass percentage:

[0007]

[0008] According to the above scheme, the pore size of the microporous corundum powder is distributed between 0.1-1 μm, and the apparent porosity is ≤8%.

[0009] According to the above scheme, in the microporous corundum powder, Al 2 O 3 ≥98%, volume density ≤3.4g / cm 3 .

[0010] According to the above scheme, in the activated alumina powder, a-Al 2 O 3 Content ≥99%, Fe 2 O 3 ≤0.1%, R 2 O≤0.1%, d50 is 1.4-1.8μm.

[0011] According to the above scheme, the silicon oxynitride microcrystalline powder is a kind of silicon nitride microcrystalline powder whose main component is Si 2 N 2 O and Si 3 N 4 The composite microcrystalline powder mainly exists in amorphous and microcrystalline forms, among which Si 2 N 2 The O content is between 40-50%.

[0012] According to the above scheme, the average diameter of the alumina fiber is 2-4 μm and the length is 0.2-0.5 mm.

[0013] According to the above scheme, in the alumina fiber, Al 2 O 3 Content ≥95%, SiO 2 ≤5%,Fe 2 O 3 ≤0.1%.

[0014] According to the above scheme, the silicon aluminum alloy powder is an alloy powder with Si≤40%, Al≥55% and a particle size≤0.074mm.

[0015] According to the above scheme, the carbon black N990 is a high-purity carbon black with a particle size d50 of 2-5 μm and a main chemical component C content of ≥98%.

[0016] According to the above scheme, the pH value of the acidic zirconium oxide sol solution is 3-5.

[0017] According to the above scheme, the acidic zirconium oxide sol is a transparent sol-like aqueous liquid, wherein the zirconium oxide particle size is less than 10nm, ZrO 2 Content 10-15%.

[0018] According to the above scheme, the polyacrylate ammonium salt dispersant is an anionic polymer dispersant.

[0019] A method for preparing the above-mentioned refractory slurry for blast furnace ceramic cup is provided, comprising the following steps:

[0020] After uniformly mixing microporous corundum fine powder 0.074-0mm, activated alumina powder, alumina fiber, silicon aluminum alloy powder, silicon oxynitride composite powder, carbon black N990 and polyacrylate ammonium salt dispersant, add acidic zirconium oxide liquid sol and stir to make it into a homogeneous slurry with good fluidity, that is, refractory mud for blast furnace ceramic cups.

[0021] According to the above scheme, the stirring and mixing time is 8-10 minutes.

[0022] A construction method for the above-mentioned refractory slurry for blast furnace ceramic cup is provided, comprising the following steps:

[0023] 1) First, the blast furnace ceramic cup prefabricated parts or bricks are positioned and laid according to the construction specifications to obtain the blast furnace ceramic cup masonry, wherein the gap between the prefabricated parts, between the bricks, or between the prefabricated parts and the bricks is left with 1.5 mm;

[0024] 2) Then, the inner surface of the obtained blast furnace ceramic cup masonry is fully covered with a film, and sandbags are used to press the surface of the film and the surrounding areas to ensure that the blast furnace ceramic cup masonry forms a closed space; vacuum holes are reserved on the surface of the blast furnace ceramic cup masonry in four directions around the blast furnace ceramic cup masonry, and a vacuum pumping device is connected; and a grouting hole is reserved at the center of the inner surface of the bottom of the ceramic cup masonry body, and a grouting device is connected;

[0025] 3) Start the vacuum equipment to perform vacuuming, and then start the grouting equipment. The mud flows through the reserved grouting holes to fill the gaps in the ceramic cup masonry. After the filling is completed, the vacuum state is still maintained for 30-60 minutes to complete the construction.

[0026] According to the above scheme, the vacuum pressure is set to 0.2-0.3MPa.

[0027] According to the above scheme, the adhesive film, the blast furnace ceramic cup masonry and the blast furnace bottom form a closed space.

[0028] The present invention provides a refractory slurry for a blast furnace ceramic cup, which uses microporous corundum powder, silicon aluminum alloy powder, silicon oxynitride microcrystalline powder, activated alumina powder, carbon black fine powder, alumina fiber, polyacrylate ammonium salt, zirconium oxide sol and the like as main raw materials to obtain a refractory slurry with high self-flowing performance; wherein:

[0029] The present invention uses polyacrylate ammonium salt as a dispersant, which is adsorbed on the surface of aluminum oxide microparticles and generates electrostatic repulsion to disperse them, thereby preventing mud from settling and coarsening, greatly reducing the viscosity of the mud, and making the mud have a self-leveling effect while reducing the amount of mud stirring and liquid addition; at the same time, the dispersant is completely volatilized during the product roasting process, and does not affect the physical and chemical properties of the product in the later stage.

[0030] The present invention introduces elemental silicon and elemental aluminum in the form of silicon-aluminum alloy, so that they can be more evenly dispersed in the refractory mud, which is conducive to the subsequent reaction to generate a ceramic phase that can be evenly distributed in the mud. At the same time, the acidic zirconium oxide sol solution oxidizes the surface of the metal aluminum to form an aluminum oxide film, which inhibits the metal aluminum from hydrating and generating gas at room temperature and causing the mud to swell and loosen. In addition, the melting point of silicon is 1420°C, and the melting point of aluminum is 660°C. The silicon-aluminum alloy powder is evenly dispersed and melts at high temperature to form a high-temperature liquid phase, which wets carbon black, silicon oxynitride microcrystalline composite powder, aluminum oxide micropowder, etc., promotes its continuous reaction in a larger temperature range, and generates a large amount of high-temperature ceramic phases such as silicon carbide, aluminum carbide, and sialon. The generated ceramic phase fills the pores left after the evaporation of the mud water, reduces the large pores in the mud, forms a ceramic-bonded mud with a large number of micropores, and improves the density and strength of the mud.

[0031] In addition, the liquid phase formed by silicon-aluminum alloy powder at high temperature is combined with the tough structure of alumina fiber at high temperature. At the same time, the phase change toughening of zirconium oxide is used to buffer the expansion of the ceramic cup during heating and high-temperature service. The refractory mud still has a good solid phase toughness structure at high temperature, which effectively buffers the thermal stress of the ceramic cup masonry and ensures the structural integrity of the ceramic cup throughout the service stage.

[0032] The invention provides a construction method for refractory mud for blast furnace ceramic cups. The outer surface of the blast furnace ceramic cup masonry is surrounded by carbon bricks, steel shells, etc., and the inner surface is covered with a rubber film and fixed and compacted with sandbags, so as to ensure that the blast furnace ceramic cup masonry forms a closed space. Then, the high fluidity of the refractory mud is utilized, and vacuum is drawn. When grouting the mud, the mud can only flow in the brick joints to fill the gaps, thereby ensuring that the mud fully fills the gaps in the ceramic cup, improving the density of the masonry, effectively reducing the gaps in the masonry from 3 mm to 1.5 mm, reducing the amount of mud used, and improving the performance of the ceramic cup.

[0033] The beneficial effects of the present invention are as follows:

[0034] 1. The present invention provides a refractory mud for blast furnace ceramic cups, which has low viscosity and high self-flowing performance. Under a high-temperature reducing atmosphere, a large number of reactions occur between the phases to form a homogeneously distributed high-strength and high-melting-point ceramic binding phase. The generated new substances are evenly distributed in a staggered manner to fill the large pores formed by the volatilization of the liquid phase, thereby reducing the large pores in the mud and forming a large number of micropores, making the mud high-strength and densified. At the same time, the mud still has a good solid-phase toughness structure at high temperatures, which can effectively buffer the thermal stress of the ceramic cup masonry and ensure the structural integrity of the ceramic cup during the entire service stage, and has broad application prospects.

[0035] 2. The present invention provides a construction method for refractory mud for blast furnace ceramic cups. The high self-flowing property of the refractory mud of the present invention is utilized to change the traditional ceramic cup construction method, forming a new construction method in which all ceramic cup bricks are first installed to the specified positions according to a predetermined sequence, and then high-fluidity refractory mud is injected by vacuum pumping to fill the gaps between the ceramic cup bricks. The drawbacks of traditional masonry construction are avoided, and the masonry gap is reduced from 3 mm to 1.5 mm, thereby reducing the possibility of molten iron penetrating through the brick joints, reducing the amount of refractory mud used, and increasing the content of masonry bricks with better high-temperature performance per unit volume; at the same time, the slurry is ensured to fully fill the gaps in the ceramic cup, thereby improving the density of the masonry, reducing the possibility of high-temperature molten iron penetrating through the mud, and improving the construction efficiency and construction quality. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The raw materials used in this embodiment are:

[0038] Microporous corundum fine powder Al 2 O 3 :98.3%, particle size 0.074-0mm; pore size distribution between 0.1-1μm, apparent porosity ≤8%, bulk density ≤3.4g / cm 3 .

[0039] Activated Alumina Powder Al 2 O 3 :99.4%,Fe 2 O 3 ≤0.1%, R 2 O≤0.1%, particle size d50=1.72um.

[0040] Silicon oxynitride microcrystalline powder is a kind of powder with Si as the main component. 2 N 2O and Si 3 N 4 The composite microcrystalline powder mainly exists in amorphous and microcrystalline forms, among which Si 2 N 2 O: 49.2%, Si 3 N 4 :35.1%, particle size d90=4.7um.

[0041] The average diameter of alumina fiber is 3μm, the length is 0.2-0.5mm, Al 2 O 3 Content 95.3%, SiO 2 4.1%,Fe 2 O 3 ≤0.1%,

[0042] Silicon aluminum alloy powder, Si content 37.3%, Al content 59.1%, particle size 0.044-0mm.

[0043] Carbon black N990 particle size d50 = 2.47 um, carbon content: 98.5%.

[0044] Ammonium polyacrylate dispersant: industrial reagent.

[0045] Liquid binder: zirconium oxide sol solution, ZrO 2 Content: 14.5%, zirconium oxide particle size distribution is about 5-10nm, pH value is 3-5.

[0046] In an embodiment of the present invention, a method for preparing refractory slurry for blast furnace ceramic cups comprises the following steps:

[0047] After uniformly mixing the components except the zirconium oxide liquid sol in a mixer, add the zirconium oxide liquid sol and stir and mix for 10 minutes to form a homogeneous slurry with good fluidity, that is, the refractory slurry for blast furnace ceramic cups is obtained.

[0048] Example 1

[0049] Provided is a refractory slurry for a blast furnace ceramic cup, wherein the raw material components are, by mass percentage:

[0050]

[0051] The test results of the performance indicators of the refractory slurry for ceramic cups provided in this embodiment are shown in Table 1.

[0052] Example 2

[0053] Provided is a refractory slurry for a blast furnace ceramic cup, wherein the raw material components are, by mass percentage:

[0054]

[0055] The performance index test results of the refractory slurry for ceramic cups provided in this embodiment are shown in Table 1.

[0056] Example 3

[0057] Provided is a refractory slurry for a blast furnace ceramic cup, wherein the raw material components are, by mass percentage:

[0058]

[0059]

[0060] Example 4

[0061] Provided is a construction method for refractory slurry for blast furnace ceramic cups, comprising the following steps:

[0062] 1) Install the blast furnace ceramic cup prefabricated parts or bricks to the blast furnace ceramic cup masonry at the specified position according to the construction requirements, leaving a gap of 1.5mm between the prefabricated parts, between the bricks, or between the prefabricated parts and the bricks;

[0063] 2) Then, the inner surface of the obtained blast furnace ceramic cup masonry is fully covered with adhesive film, and sandbags are used to press the surface of the adhesive film and the surrounding areas to ensure that the blast furnace ceramic cup masonry forms a closed space; vacuum air holes are reserved on the upper surface in four directions around the blast furnace ceramic cup masonry, and the vacuum equipment is connected; and grouting air holes are reserved at the center of the inner surface of the bottom of the ceramic cup masonry body, and the grouting equipment pipeline is connected.

[0064] 3) The vacuum pressure is set to 0.2MPa, and the vacuum equipment is started to vacuum for 5 minutes, and then the grouting equipment is started to flow the refractory slurry obtained in the embodiment of the present invention from the reserved grouting hole through the pipeline to fill the gap of the ceramic cup masonry body. After the filling is completed, the vacuum state is still maintained for 60 minutes to allow the slurry to fully impregnate the bricks or prefabricated parts and dehydrate and dry. After closing the equipment, remove the film, sandbags and other equipment, and the construction process is completed.

[0065] Comparative Example 1

[0066] Provided is a refractory slurry for a blast furnace ceramic cup, wherein the raw material components are, by mass percentage:

[0067]

[0068] The performance index test results of the refractory slurry for ceramic cups provided in this comparative example are shown in Table 1.

[0069] Comparative Example 2

[0070] Provided is a refractory slurry for a blast furnace ceramic cup, wherein the raw material components are, by mass percentage:

[0071]

[0072]

[0073] The performance index test results of the refractory slurry for ceramic cups provided in this comparative example are shown in Table 1.

[0074] Comparative Example 3

[0075] Provided is a refractory slurry for a blast furnace ceramic cup, wherein the raw material components are, by mass percentage:

[0076]

[0077] Silica sol (SiO 2 Content 30%, PH value: 8-10) plus 13.1%.

[0078] The performance index test results of the refractory slurry for ceramic cups provided in this comparative example are shown in Table 1.

[0079] Comparative Example 4

[0080] Provide a traditional non-fluid mud, the raw material components are as follows by mass percentage:

[0081]

[0082] The performance index test results of the refractory slurry for ceramic cups provided in this comparative example are shown in Table 1.

[0083] The comparative slurry has good plasticity and no fluidity, and can only be constructed by masonry method, with the construction joint designed to be 3mm.

[0084] Table 1. Test results of refractory slurry properties prepared in Examples and Comparative Examples

[0085]

[0086]

[0087] Table 1 shows that the refractory slurry obtained in the embodiment of the present invention has good fluidity, and can realize slurry pouring and filling construction; the microporosity in the slurry is high and the large pores are few, so molten iron is not easy to penetrate through the micropores, and the thermal conductivity of the slurry is reduced, so that the 1150°C isotherm is blocked in the ceramic layer; the slurry has high bonding strength, so that it can sinter and bond the ceramic cup at high temperature to form a solid whole; the molten iron melting index is low, and the slurry has strong resistance to molten iron erosion.

[0088] In summary, the present invention adopts polyacrylic acid ammonium salt as a dispersant of alumina powder to prepare a high-fluidity refractory mud, so that the refractory mud can be infiltrated into the gap of the ceramic cup by vacuum infusion, changing the traditional masonry construction method, so that the gap of the mud in the ceramic cup can be reduced from 3mm to 1.5mm to meet the construction requirements, thereby reducing the contact area between the mud and the molten iron in the ceramic cup structure, and reducing the risk of molten iron leaking from the mud gap. Silicon oxynitride microcrystalline powder, silicon aluminum alloy powder, alumina powder, and carbon black powder are used as the main sintered materials, and acidic zirconium oxide sol is used as a binder for high-fluidity refractory mud, so that the mud reacts in large quantities to form a high-strength and high-melting-point ceramic bond, and the new material generated by the reaction is filled to make the mud have a higher microporosity, and the 1150°C isotherm (i.e., the molten iron solidification line) is blocked in the ceramic layer, so that the carbon brick avoids the brittle fracture zone of 800-1100°C. The above measures work together to create a new type of refractory slurry and a new construction method, which effectively improves the use effect of ceramic cups.

[0089] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A refractory slurry for blast furnace ceramic cup, characterized in that: In terms of mass percentage, the raw material components are:

2. The refractory slurry according to claim 1, characterized in that: The pore size of the microporous corundum powder is distributed between 0.1 and 1 μm, and the apparent porosity is ≤8%.

3. The refractory slurry according to claim 1, characterized in that: The microporous corundum powder has Al2O3≥98% and a volume density≤3.4g / cm 3 ; In the activated alumina powder, the a-Al2O3 content is ≥99%, Fe2O3≤0.1%, R2O≤0.1%, and d50 is 1.4-1.8μm; in the alumina fiber, the Al2O3 content is ≥95%, SiO2≤5%, and Fe2O3≤0.1%.

4. The refractory slurry according to claim 1, characterized in that: The silicon oxynitride microcrystalline powder is a composite microcrystalline powder whose main components are Si2N2O and Si3N4, and mainly exists in amorphous and microcrystalline forms, wherein the content of Si2N2O is between 40-50%.

5. The refractory slurry according to claim 1, characterized in that: The alumina fibers have an average diameter of 2-4 μm and a length of 0.2-0.5 mm.

6. The refractory slurry according to claim 1, characterized in that: The silicon aluminum alloy powder is an alloy powder with Si≤40%, Al≥55% and a particle size≤0.074 mm.

7. The refractory slurry according to claim 1, characterized in that: The pH value of the acidic zirconium oxide sol solution is 3-5.

8. The refractory slurry according to claim 1, characterized in that: In the acidic zirconium oxide sol, the particle size of zirconium oxide is below 10 nm and the content of ZrO2 is 10-15%.

9. A method for preparing refractory slurry for blast furnace ceramic cup according to any one of claims 1 to 8, characterized in that: The following steps are involved: After uniformly mixing microporous corundum fine powder 0.074-0mm, activated alumina powder, alumina fiber, silicon aluminum alloy powder, silicon oxynitride composite powder, carbon black N990 and polyacrylate ammonium salt dispersant, add acidic zirconium oxide liquid sol and stir to make it into a homogeneous slurry with good fluidity, that is, refractory mud for blast furnace ceramic cups.

10. A construction method for refractory slurry for blast furnace ceramic cup according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) First, the blast furnace ceramic cup prefabricated parts or bricks are positioned and laid according to the construction specifications to obtain the blast furnace ceramic cup masonry, wherein the gap between the prefabricated parts, between the bricks, or between the prefabricated parts and the bricks is left with 1.5 mm; 2) Then, the inner surface of the obtained blast furnace ceramic cup masonry is fully covered with a film, and sandbags are used to press the surface of the film and the surrounding areas to ensure that the blast furnace ceramic cup masonry forms a closed space; vacuum holes are reserved on the surface of the blast furnace ceramic cup masonry in four directions around the blast furnace ceramic cup masonry, and a vacuum pumping device is connected; and a grouting hole is reserved at the center of the inner surface of the bottom of the ceramic cup masonry body, and a grouting device is connected; 3) Start the vacuum equipment to perform vacuuming, and then start the grouting equipment. The mud flows through the reserved grouting holes to fill the gaps in the ceramic cup masonry. After the filling is completed, the vacuum state is still maintained for 30-60 minutes to complete the construction.

Citation Information

Patent Citations

  • Zirconium sol reinforced corundum-mullite product and production method thereof

    CN101830717A

  • Method for reinforcing sandy soil and improving engineering properties of sandy soil through vacuum-pumping technology

    CN106836176A

  • Alumina-carbon drain hole brick toughened with homogenizing material and production method thereof

    CN107473759A

  • Device for cracked part cleaning and crack repairing of underwater membrane bag concrete wall and construction method

    CN111042232A

  • Refractory material for refractory layer of deacidification furnace and preparation method of refractory material

    CN114380609A